Research on the Development and Publishing Strategy of Intelligent Chinese Textbooks in the Era of Convergent Media - Wu, Bingzhang (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
In the era of convergent media, technological innovations have provided new opportunities for the transformation, development, and publication of international Chinese textbooks. Currently, the development and publication of intelligent Chinese textbooks are in their infancy, facing challenges such as uneven digital textbook development levels across countries, insufficient interactivity, significant disparities in the number of country-specific intelligent textbooks, imprecise positioning in textbook development and publication, low levels of "intelligence" in textbooks, and poor compatibility with platform users. By leading with technology, accelerating the integration and innovation of various digital education resources, fostering collaborative construction, and creating a community for the development of Chinese textbooks integrating science and education, we can establish paradigms and improve the diversified system for the development and publication of intelligent textbooks. This will provide "material" support for the sustainable development of international Chinese education.